Safety and effectiveness of baloxavir marboxil for the treatment of influenza in Japanese clinical practice: A postmarketing surveillance of more than 3000 patients. Issue 7 (July 2020) - Nakazawa, Masami; Hara, Kanae; Komeda, Takuji; Ogura, Eriko
Abstract: Baloxavir marboxil is an oral anti-influenza drug that inhibits the cap-dependent endonuclease of the virus polymerase acidic protein. In clinical trials, baloxavir reduced the time to alleviation of influenza symptoms and time to resolution of fever in adults, adolescents, and children. The purpose of this study is to collect data on the safety and effectiveness of baloxavir when used in clinical practice. This postmarketing surveillance (clinicaltrials.jp; JapicCTI-183882), conducted at 688 Japanese hospitals or clinics (March 2018 to March 2019), enrolled patients of any age with influenza A or B infection who received a single, weight-based dose of baloxavir. Adverse drug reactions (ADRs) were seen in 11.2% of 3094 patients during the 7-day observation period; the most common ADR was diarrhea (6.1%). ADRs were more common in children aged <12 years (14.1%) than in adults (10.0%). Almost all ADRs were non-serious (98.9%) and were recovered or recovering (96.7%). Median time to alleviation of symptoms (N = 2884) was 2.5 days (overall, influenza A, and influenza B groups). Median time to resolution of fever (N = 2946) was 1.5 days (overall, influenza A, and influenza B groups). Biphasic fever (increased temperature after previous fever resolution) was seen in 6.7% of patients overall and 28.6% of patients <6 years infected with influenza B, similar to rates published elsewhere with other influenza drugs and in untreated influenza. This postmarketing surveillance of >3000 patients suggests that baloxavir is well tolerated and effective regardless of patient age or influenza virus type.